2009
DOI: 10.21273/jashs.134.6.632
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Male-sterile Line Bcajh97-01A/B and Identification of Candidate Genes for Genic Male Sterility in Chinese Cabbage-pak-choi

Abstract: Cytological features of ‘Aijiaohuang’ chinese cabbage-pak-choi (Brassica campestris ssp. chinensis) Bcajh97-01A/B genic male-sterile AB line were examined to determine phenotypic reasons for male sterility. The sterile line Bcajh97-01A was found to undergo aberrant cytokinesis during male meiosis. Transcriptional profiling of the flower buds of both fertile and sterile plants was performed at the periods preceding meiosis, at the tetrad to uninuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Cytological observations of anther development showed that the pollen mother cells are formed normally in the sterile line, but the following cycle of meiosis is disturbed and the anther fails to form tetrads. From then on, the content of the microspore begins to degenerate and consequently forms aborted mature pollen grains only coated with a defective exine wall (Huang et al ., , b). Thus, use of the ‘Bcajh97‐01A/B’ GMS A/B line is a good system to study the genes expressed during pollen development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytological observations of anther development showed that the pollen mother cells are formed normally in the sterile line, but the following cycle of meiosis is disturbed and the anther fails to form tetrads. From then on, the content of the microspore begins to degenerate and consequently forms aborted mature pollen grains only coated with a defective exine wall (Huang et al ., , b). Thus, use of the ‘Bcajh97‐01A/B’ GMS A/B line is a good system to study the genes expressed during pollen development.…”
Section: Resultsmentioning
confidence: 99%
“…This makes the material a good system to study gene expression during pollen development. Differences in the expression of transcripts including protein‐coding genes and miRNAs had been revealed between fertile and sterile floral buds in our previous studies, and many candidate genes had been characterized (Huang et al ., , ,b; Jiang et al ., ; Lin et al ., , ). Here, the discovery of a set of differentially expressed lncRNAs between fertile and sterile plants provides an additional important intriguing clue to understand the regulation of male fertility in B. rapa .…”
Section: Discussionmentioning
confidence: 99%
“…chinensis Makino) GMS A/B line system, which is named ‘ Bcajh97-01A/B ’. The only difference between A/B lines is that the male sterile plant (‘ Bcajh97-01A ’) undergoes an aberrant meiotic cytokinesis at the microsporogenesis stage and thus could not produce any functional mature pollen [ 42 , 43 ]. Therefore, we used the RNA-seq data of ‘ Bcajh97-01A/B ’ to identify the male fertility-related CCCH genes in B. campestris [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The progenies of ‘ Bajh97 - 01A / B ’ were segregated into a homozygous male sterile line ( Bcajh97 - 01A ) and a heterozygous male fertile line ( Bcajh97 - 01B ) with a 1:1 ratio. The only difference presented between the sibling (sister) lines is that ‘ Bcajh97 - 01A ’ is in a complete absence of mature pollen compared with that of ‘ Bcajh97 - 01B ’ [ 61 , 62 ]. This feature makes ‘ Bajh97 - 01A / B ’ become an ideal material to explore the genes closely related to pollen development.…”
Section: Methodsmentioning
confidence: 99%